FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN CAPAIAN RENCANA ANGGARAN PADA SATUAN KERJA PERANGKAT DAERAH DI KABUPATEN BENGKAYANG (Studi Kasus pada BPPKB Kabupaten Bengkayang) - B2051131009, ELISABET PONDOK (Jurnal Ekonomi Daerah (JEDA), 2017)
The study entitled “Factors Affecting the Success Achievement Budgetingplan on Working Unit in Bengkayang Regency(the Case Study on BPPKB Bengkayang)" is a descriptive study aimed to analyze the factors that affect the basis for determining spending needs activities on working unit (BPPKB)of Bengkayang regency and implementation of the budget in realizing the targets and achievements of the action plan is determined. The study used a qualitative approach, matching between theory, empirical with the circumstances that occurred on the object of research. Using primary data observations and interviews and secondary data in the form of reports, documents of development planning and budgeting in the period 2011-2015 year in BPPKB Bengkayang working unit. It is known that factors that influence the success of a budget plan is to budget constraints, the limited human resources (HR), the lack of legislative support. In determining the budget plan refers to the Strategic plan and working plan on each field unit, which is adapted to the theory of Performance-Based Budgeting (ABK), outlined in the submission form RKA. To ensure accountability and transparency in the system ABK, then made the program the success indicators of performance indicators, especially the outcomes stated in the document that is contained in the target indicators DPA-SKPD. The target indicators are results (outcomes) expected of the financing will be carried out which can then be measured his achievement. Implementation of budgeting has been in accordance with the procedure of preparing the budget so that the resulting level of achievement shows the optimal result means have met the target that has been determined in the strategic plan and (worki planing) of BPPKB Bengkayang regency. Keywords : Strategic plan, working plan, Budget Plans, Performance, value of money